Brain Functional and Structural Changes in Alzheimer's Disease With Sleep Disorders: A Systematic Review - Liu, Yong-shou; Wang, Yong-ming; Zha, Ding-jun (Frontiers in Psychiatry, 2021)
Introduction: Sleep disorders (SLD) is supposed to be associated with increased risk and development of Alzheimer’s disease (AD), and patients with AD are more likely to show sleep disorders. However, neurobiological performance of patients with both AD and SLD in previous studies is inconsistent, and identifying specific patterns of brain functional network and structural characteristics in this kind of comorbidity is warranted for understanding how the AD and SLD symptoms interact with each other, as well as finding effective clinical intervention. Thus, the aims of this systematic review were to summarize the relevant findings and their limitations, provide future research directions. Methods: A systematic search on brain functional and structural changes in patients with both AD and SLD was conducted from PubMed, Web of Science and EMBASE databases. Results: Nine original articles published between 2009 and 2021 were included, with a total of 328 patients with comorbid AD and SLD, 367 patients with only AD, and 294 healthy controls. One Single-photon emission computed tomography and one multi-slice spiral computed tomography perfusion imaging studies investigated changes of cerebral blood flow; four structural magnetic resonance imaging (MRI) studies investigated brain structural changes, two of them used whole brain analysis and another two used regions of interests; two resting-state functional MRI studies investigated brain functional changes; and one 2-deoxy-2-(18F)fluoro-d-glucose positron emission tomography (18F-FDG-PET) investigated 18F-FDG-PET uptake in patients with comorbid AD and SLD. Findings were inconsistent, ranged from default mode network to sensorimotor cortex, hippocampus, brain stem and pineal gland, which may be due to different imaging techniques, measurements of sleep disorder and subtypes of AD and SLD. Conclusions: Our review provides a systematic summary and promising implication of specific neuroimaging dysfunction underlies cooccurrence of AD and SLD. However, limited and inconsistent findings still restrict its neurobiological explaination. Further studies should use unified standards and comprehensive brain indices to investigate the pathophysiological basis of interaction between AD and SLD symptoms in the development of the disease spectrums.